DINAMIKA LEMBAGA PENDIDIKAN ISLAM DI INDONESIA, TINJAUAN HISTORIS - Hakim, Dani Amran (UNISAN JURNAL, 2024)
The purpose of this study is to investigate the historical dynamics of Islamic educational institutions in Indonesia. Based on a thorough analysis of the literature as well as acquired knowledge from numerous reliable primary book sources, this work was prepared. Even though Islamic boarding schools were not originally regarded as official legal education, the research findings demonstrate that they represent the historical origins of Islamic education in Indonesia. However, there have been a number of remarkable occurrences in society as a result of the dynamics surrounding the growth of Islamic boarding school education. Islamic education is beginning to quickly grow in a modern and contemporary manner, much like Muhammadiyah, Nahdlatul Ulama (NU), Al-Irsyad, Jamiyyatul Al-Washliyah, and others. This is social, religious, educational, and da’wah. The numerous excellent solutions offered address issues facing the country and state as well as our Islamic boarding schools, madrasas (MI), MTs, MA, and even Islamic universities (PTI). To relieve the country of several issues, the practical advancement of Islamic education must coincide with national strategy in the future. Then a number of development plan elements were implemented, including the foundation of national development, multicultural Islamic education, resource development organizations, stressing the fundamental goal of "li utammima makarimal akhlaq," and spiritualization of the national character.